Role of alanine aminotransferase in determining the biliary etiology in acute pancreatitis - Shailesh Simkhada (Society of Surgeons of Nepal, 2016)
Background: Acute pancreatitis (AP) is a common surgical presentation and a leading cause of morbidity and mortality worldwide. Gallstones and excessive alcohol consumption are the most frequent causes of AP. Aim of this study was to investigate the predictive value of raised ALT (Alanine aminotransferase) in determining biliary etiology in patients presenting with acute pancreatitis.